2011
DOI: 10.1111/j.1863-2378.2011.01407.x
|View full text |Cite
|
Sign up to set email alerts
|

Sonographical and Serological Survey of Human Cystic Echinococcosis and Analysis of Risk Factors Associated with Seroconversion in Rural Communities of Kerman, Iran

Abstract: Cystic echinococcosis (CE) caused by larval stage of Echinococcus granulosus, is an endemic zoonosis in Iran particularly in rural regions. The objective of this study was to determine the prevalence of CE among rural communities in Kerman using ultrasonography (US) and serology. Kerman Province, in southeastern Iran, is the largest province, with 2.9 million inhabitants. A sample of 1140 individuals (200 males and 940 females) was selected by randomized cluster sampling in 2006-2008. After acquiring informed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 24 publications
6
41
2
Order By: Relevance
“…False-positive serological results may also be returned in non-active disease stages, during pregnancy, and in patients with autoimmune or malignant diseases (34). Finally, women seem to be more frequently affected by E. granulosus infections (38).…”
Section: Discussionmentioning
confidence: 99%
“…False-positive serological results may also be returned in non-active disease stages, during pregnancy, and in patients with autoimmune or malignant diseases (34). Finally, women seem to be more frequently affected by E. granulosus infections (38).…”
Section: Discussionmentioning
confidence: 99%
“…Source of domestic water was described as a significant risk factor for human CE in Jordan (Dowling et al, 2000). It has been suggested that in Muslim countries dog ownership is not a major risk factor for human infection because the major risk in these countries arises from high levels of environmental contamination with dog faeces due to high numbers of stray dogs (Dowling et al, 2000;Harandi et al, 2011). In the case of Syria, current prevalence data regarding human infection are not available and detailed epidemiological studies are required from this country.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…The parasite circulates primarily among domestic dogs (owned and stray animals) as definitive hosts and a variety of domestic livestock as intermediate hosts (Dowling et al, 2000;Harandi et al, 2011;Rafiei et al, 2007;Shariatzadeh et al, 2015). However, a wild animal cycle has been documented in Iran and Turkey involving wolf, jackal, hyena and red fox as definitive hosts, and wild sheep (Ovis orientalis) and the goitered gazelle (Gazella subgutturosa) as intermediate hosts (Dalimi et al, 2002(Dalimi et al, , 2006Eslami et al, 1981Eslami et al, , 2016Simsek and Eroksuz, 2009).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest rate of infection was found in 40-60 year old age group with 1.8 % and the least rate was in 20-40 year old age group as 0 %. In Golestan (North of Iran) and Kerman (Southeast) Provinces, the highest rates of the disease were observed in 30-60 and 20-30 year old age groups, respectively (Harandi et al 2011;Baharsefat et al 2007). In fact, hydatidosis is considered as a chronic disease of long incubation period (might be 20-30 year) and accordingly a wide range of different ages is noticeable in infected individuals (Torgerson and Deplazes 2009).…”
Section: Discussionmentioning
confidence: 99%